Raptor Acupuncture for Treating Chronic Degenerative Joint Disease - Keum Hwa Choi; Gail Buhl; Julia Ponder (Medical Association of Pharmacopuncture Institute, 2016)
A permanently captive 21-year-old male bald eagle was diagnosed with chronic degenerative joint disease in the right stifle with severe lameness (Grade 5) based on radiography. Clinical signs included decreased movement, vocalization, non weight-bearing on the affected limb, inappetence, depression, and pododermatitis on the left foot (bumblefoot, Grade 3). The eagle was treated with anti-inflammatory or analgesic drugs including carprofen and celecoxib. As there was no observed clinical improvement with any of the treatments, acupuncture treatment was provided. The eagle was treated with dry needle acupuncture once per week for 2 months and biweekly for another 2 months. The Traditional Eastern Medicine diagnosis of this eagle was Bony Bi syndrome. The selected acupuncture points were ST 36, LI 4, BL 40, BL 60, GB 34, and Ba Feng (Table 3). The lameness score improved from Grade 5 to Grade 1 after 4 months of acupuncture treatment. The observed pododermatitis improved from Grade 3 to Grade 0. Symptoms including inappetence and vocalizations were significantly reduced over the 4 month period. There was no significant improvement in the radiographic signs. In conclusion, acupuncture may be a potential medical option for permanently captive raptors having musculoskeletal conditions, such as degenerative joint disease.